Preservative effects of aqueous and ether extracts of Aframomum melegueta on West African soft cheese - Badmos, AA; Imam, AA; Annongu, AA; Yusuff, AT; Kayode, RMO; Salami, KO; Ahutu, IA; Lawal, AO (Bangladesh Journal of Animal Science, 2017)
The Total Bacterial Count, proximate composition, and sensory evaluation of West African Soft Cheese supplemented with aqueous and ether extracts of the spice Aframomum melegueta (at 0%, 1%, 2% and 3% each) were determined with a completely randomized design. Effects of the spice were monitored for 3 days. The results revealed that 3% concentration of the ether extract of the spice was the most inhibitory (p<0.05) of microbial growth for the duration of the experiment and it also significantly improved the fat, ash and protein contents of the cheese. The study recommended the addition of 3 % ether extract of A. melegueta as an additive to fortify West African soft cheese. Bang. J. Anim. Sci. 2017. 46 (1): 51-56